Le sens du mot « autrui » dans l'article 1053 du Code Civil et l'affaire « Régent Taxi » - Robinson, Ann (Les Cahiers de droit, 1978)
The case of Regent Taxi has given rise to considerable debate in the interpretation of the word « another» and whether it should be read restrictively or given a wide meaning. In a thorough analysis of the majority and minority opinions of the Supreme Court decision, an attempt has been made to circumscribe the positions adopted. Thereafter, an analysis of subsequent cases has been carried out to establish whether the majority views expressed by the Supreme Court have settled the debate definitely of whether the question remains unresolved.